Viabilidade da utilização do óleo de baru na síntese de poliuretanas - Rosa, Gabriel Marques (2020)
In this work, the feasibility of using oil extracted from baru seeds in the synthesis of polyurethanes was studied. From raw seeds purchased from traders in the city of Iporá located in the state of Goiás, the oil was extracted and in order to study the polyol obtained, a factorial design 22 was carried out, changing the synthesis conditions. The bio-polyols obtained were then characterized via Acidity Index (IA), Hydroxyl Index (IOH), Fourier Transform Infrared Spectroscopy (FTIR), Nuclear Magnetic Resonance (NMR), Differential Scanning Calorimetry (DSC) and Gravimetry Term (TG). It was possible to observe that baru oil polyols were synthesized in all studied conditions, obtaining different levels of hydroxylation, diversifying its use. The preparation of the polymeric materials involved polyaddition reactions of a polyol (Baru biopolyols obtained under different synthesis conditions) and an isocyanate (TDI, mixture of isomers). The formation of polyurethanes was confirmed by Infrared Spectroscopy with Fourier Transform, where all samples had hydrogen bonds in the NH groups of the polyurethane, the low frequency (around approximately 3370 cm-1) evidences hydrogen bonds between the rigid and flexible. The DSC results demonstrated that there is an increase in Tg for polyurethanes synthesized with more hydroxylated bio-polyols, thus producing more rigid polyurethanes. SEM analyzes revealed polyurethanes with different morphologies, the presence of heterogeneous shapes and sizes on the polymer surfaces. Therefore, the results obtained demonstrated that the synthesis conditions generate polyols with different degrees of hydroxylation resulting in polyurethanes with different characteristics.